Her highlander for one night - Brisbin, Terri (Brisbin, Terri. Highland feuding, 2022)
"When Glynnis had to make a noble marriage, Iain Mackenzie Cameron's illegitimacy stood in the way. She married another--but now she's returned to the clan a widow, and Iain is an assured warrior, the chieftain's heir. Glynnis would make him a more than suitable bride--except for her inability to produce heirs. Iain must marry elsewhere--but only after she claims one precious impassioned night with him!"--Amazon.com.